2022
DOI: 10.1021/acsanm.1c04165
|View full text |Cite
|
Sign up to set email alerts
|

BiOCl Nanorings with Co-Exposed (110)/(001) Facets for Photocatalytic Degradation of Organic Dyes

Abstract: A BiOCl nanoring with co-exposed (110)/(001) facets is presented, which is prepared by selectively etching (001) facets of BiOCl nanosheets based on a selective etching mechanism. The BiOCl nanorings display a high photocatalytic performance toward organic dyes including butyl rhodamine B (RhB) and methyl orange (MO). The results show that 40 mg of BiOCl nanorings can degrade 40 mL of RhB (10 mg L −1 ) in 4 min. Besides, 40 mL of 30 mg L −1 RhB can be completely degraded within 14 min. The reaction rate consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…As shown in Figure S1, the results showed that ratios of I 110 / I 102 and I 110 / I 101 are larger than that of I JCPDS , further confirming the preferred growth of (110) facet in the whole crystal-growth process, which is in agreement with literature results . Orientation growth of the (110) facet facilitates the construction of facet junction in the crystalline phase …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…As shown in Figure S1, the results showed that ratios of I 110 / I 102 and I 110 / I 101 are larger than that of I JCPDS , further confirming the preferred growth of (110) facet in the whole crystal-growth process, which is in agreement with literature results . Orientation growth of the (110) facet facilitates the construction of facet junction in the crystalline phase …”
Section: Resultssupporting
confidence: 90%
“…For instance, Peng et al and Zhao et al synthesized the (001)/(110) binary facet homojunction in BiOCl, which greatly accelerated the separation of e − −h + pairs. 22,23 Li et al developed the (001)/ (102)/(112) ternary facet junction in BiOCl to attain effective spatial separation of charge carriers, showing excellent photocatalytic performance for hydrogen production. 21 Moreover, the defects on the active facets of BiOCl nanosheets may act as reactive sites for photocatalytic reactions and enhance the performance of photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 It was considered that the current was unstable at 0-150 s at the beginning, the photocurrent would fall off because of the large size of the samples and the internal carrier separation does not reach a steady state. 47,48 The semicircle of the Nyquist plot represented the charge transfer resistance. The smaller the radius, the faster the charge was transferred.…”
Section: Optical and Electronic Propertiesmentioning
confidence: 99%
“…The defect complex of V Bi with a nearest V Cl has been calculated, which shows a small possibility of electron-hole recombination due to the small spatial overlap between the electrons and hole polarons. Ultrathin structures are designed to reduce the charge-diffusion distance so as to separate the electrons and holes efficiently 25,60 and impurity ions, such as Mn, C, N, etc., are introduced to trap carriers to inhibit electron-hole recombination and decrease the band gap to enhance visible light harvesting. 61,62 Besides, the defect O Cl serves as a photoluminescence quenching center by calculation.…”
Section: Extension To the Fully Concentrated System Bioclmentioning
confidence: 99%